Preparation and Characterization of Steam Activated Chicken Eggshell for Gaseous Pollutant Adsorption - Abdul Raheem, A. M. O.; Adeoye, E. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Air pollution is a major issue because it can immediately cause health problems. The primary pollutants are oxides of nitrogen, Sulphur, carbon, and oxidants. The collection, preparation, and characterization of chicken eggshell for the production of activated carbon useful in air purification, was carried out. The preparation was done in succession from raw uncarbonized to carbonized and then to steam activated form for adsorption of air pollutants. Powdered Eggshell was Carbonized at different temperatures in the range of 150-600 ºC to achieve optimum and effective temperature for best carbon content from its char. The best carbon yield was gotten at 450 ºC/1 hour in a carbolite type muffle furnace which gives less room for air flow. Thermal / steam activation of the carbonized eggshell was done at 500 ºC for 1 hour. The ash content, bulk density, electrical conductivity, pH, and moisture contents were analyzed respectively. The samples were characterized for their surface area and pore volume. The ash contents for the three samples were in the order Uncarbonized (41.76 %) > Carbonized (32.62 %) > Stean Activated (29.47 %) while the bulk density followed Carbonized (1. 19 g/ml) > Steam Activated (1.11 g/ml) > Uncarbonized (0.79 g/ml). All the three samples had the same value of 0.31 mS/cm for the electrical conductivity while two of the samples (carbonized and activated) had the same pH (8.1) and uncarbonized had a lower pH (7.9). The moisture contents ranged from 2 to 9 % with steam activated sample having the least and uncarbonised, the highest. Tapping density, surface area, pore volume, iodine number, % iodine absorbed values followed the order Steam active > Carbonized > Uncarbonized samples. The steam activated sample having the highest values of all these parameters showed it possesses high adsorption capacity for gaseous pollutants.